The Effect Of The Addition Of Polyvinyl Alcohol (PVA) Concentrations on the Characteristics of The Carboxymethyl Cellulose (CMC)-Poly (Acrylic Acid) Hydrogel Superabsorbent as a Planting Medium - Rahma Falah Maulidina; Dwi Pujiani; Haryanto Haryanto (Universitas Ahmad Dahlan, 2022)
Superabsorbent hydrogel is a hydrophilic network which has the ability to absorb and bind large amounts of water, but is insoluble in water. Hydrogel can be applied in various fields including medical applications, planting medium and waste absorbers. One type of hydrogel that has been widely developed is Carboxymethyl Cellulose (CMC) based hydrogel. However, CMC-based hydrogels still have several shortcomings, namely mechanical properties and low water absorption. In this study, a superabsorbent hydrogel was synthesized from CMC and acrylic acid with the addition of PVA and citric acid as a crosslinking agent and ammonium persulfate as an initiator. This research was conducted to determine the effect of PVA on the characteristics of the CMC-Poly(Acrylic Acid) hydrogel. The variation of the concentration of PVA used was 0% to 2.5% (w/v). The analyzed characteristics include gel fraction, swelling ratio, mechanical properties (tensile strength and elongation). The results showed that the addition of PVA decreased gel fraction from 60.35% to 48.68% and increased the swelling ratio from 719% to 895%. The mechanical properties of hydrogel also increased by increasing the concentration of PVA as seen in the tensile strength value (0.365 MPa to 2.165 MPa) and the percent elongation (13.96% to 30.82%). The results of the FTIR spectrum showed the presence of the OH functional group at the absorption wave number 3284.42 cm-1 and a new absorption band appeared due to the cross-linking at the wave number 1303.88 cm-1 (C-C group).